2004
DOI: 10.1371/journal.pbio.0020230
|View full text |Cite
|
Sign up to set email alerts
|

Immunity Promotes Virulence Evolution in a Malaria Model

Abstract: Evolutionary models predict that host immunity will shape the evolution of parasite virulence. While some assumptions of these models have been tested, the actual evolutionary outcome of immune selection on virulence has not. Using the mouse malaria model, Plasmodium chabaudi, we experimentally tested whether immune pressure promotes the evolution of more virulent pathogens by evolving parasite lines in immunized and nonimmunized (“naïve”) mice using serial passage. We found that parasite lines evolved in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
133
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 47 publications
10
133
0
Order By: Relevance
“…19 These studies suggest that virulence evolution may be an unintended consequence of artificial enhancement of host resistance through vaccination or drug therapy. Additionally, Mackinnon et al 18 used serial passage of rodent malaria through immunized vs. non-immunized mice to show that passage through immunized animals selects for more virulent malaria parasites. 18 Results from our experiments are in contrast to these previous studies and suggest that resistant host genotypes can favor the evolution of less generally virulent pathogens through enhanced selection for specialization in a pathogen population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 These studies suggest that virulence evolution may be an unintended consequence of artificial enhancement of host resistance through vaccination or drug therapy. Additionally, Mackinnon et al 18 used serial passage of rodent malaria through immunized vs. non-immunized mice to show that passage through immunized animals selects for more virulent malaria parasites. 18 Results from our experiments are in contrast to these previous studies and suggest that resistant host genotypes can favor the evolution of less generally virulent pathogens through enhanced selection for specialization in a pathogen population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in experimental host-pathogen systems has shown that artificial enhancement (e.g., through vaccination or drug therapy) of host resistance can favor virulent pathogen genotypes over avirulent competitors during co-infection. [17][18][19][20] Additionally, work from our lab employing serial passage of Cryptococcus neoformans (a generalist fungal pathogen) through different genotypes of inbred mice demonstrated that the host genotype a pathogen stock was serially passaged through had a significant influence on the trajectory of pathogen adaptation…”
Section: Host Resistance Influences Patterns Of Experimental Viral Admentioning
confidence: 99%
“…First, in serial passage experiments, malaria (19) and other parasites (5) often become more virulent and in live attenuated vaccines, mutants with wild-type virulence can arise (20,21). In both cases, the virulence increases could be a direct result of new virulent mutants outcompeting the variants that predominate in the current population within the host.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the large number of theoretical studies addressing within-host competition, there is no experimental evidence that virulent parasites are indeed competitively superior to prudent parasites and that virulent parasites transmit at a higher rate from mixed infections (15), two assumptions critically underlying this theory. The only evidence supporting this claim is indirect; serial passage of pathogens typically increases virulence in the host used for passage (5,19), and live attenuated vaccines occasionally revert to wild-type virulence (20,21). Both phenomena could be due to virulent variants rising in frequency, because they have a competitive advantage within hosts, but other explanations are possible.…”
mentioning
confidence: 99%
“…A series of theoretical models have investigated the impact of host immunity on the evolution of parasite virulence [71][72][73][74][75]. Rarer have been the experimental studies that have tested the predictions put forward by this theoretical work [76].…”
Section: Host Immunity and The Evolution Of Virulencementioning
confidence: 99%